Plurality within contemporary organizations. Issue 2 (2014) - Shaista E. Khilji; Edward F. Murphy; Regina A. Greenwood; Bahaudin G. Mijtaba
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to expand the burgeoning research, which provides evidence relating to the influence of religion upon work‐related values. Design/methodology/approach – The authors employed a survey methodology to collect data across seven countries and six religions. Findings – The study provides evidence of differences as well as similarities in the way people belonging to different religions rank personal values. Thus, on the one hand, the authors can argue that religion helps shape our behavior and attitudes in the workplace, whilst at the same time, however, accepting the converging influence of globalization and/or the universality of some values that they include in their analysis. This finding leads the authors to focus upon a complex pattern of value variations and similarities across religions. Originality/value – Overall, the findings provide a glimpse into what the paper interprets as (just one dimension of) plurality within contemporary organizations to support the paradox perspective, popularized by Lewis and Smith and Lewis, who contend that organizations embed multiple tensions and dilemmas in an ongoing cyclical process. Hence the paper argues that the similarities and differences across religious affiliations are not "either/or" choices but dualities that must be dynamically balanced in order to simultaneously meet multiple employee needs. The paper concludes that managers and employees need to articulate and embrace paradoxes related to religion, in order to create an awareness of the influence of religion that leads to being inclusive. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors would also like to thank the following individuals for their contribution to the paper: Sankalp Chaturvedi, Paraskevi T. Christoforou, Jaime A. Ruiz‐Gutierrez, Miguel Olivas‐Lujan, Dora M Luk, Silvia Ines Monserrat Lluna, Sergio Madero, Terrell Manyak, Neusa Maria Bastos F. Santos, William Teeple, Arnel Onesimo O. Uy and Mark D. Woodhull. </ack>